Difference between revisions of "009B Sample Final 1, Problem 4"
Jump to navigation
Jump to search
(2 intermediate revisions by the same user not shown) | |||
Line 1: | Line 1: | ||
<span class="exam"> Compute the following integrals. | <span class="exam"> Compute the following integrals. | ||
− | + | <span class="exam">(a) <math>\int \frac{t^2}{\sqrt{1-t^6}}~dt</math> | |
− | + | <span class="exam">(b) <math>\int \frac{2x^2+1}{2x^2+x}~dx</math> | |
− | + | <span class="exam">(c) <math>\int \sin^3x~dx</math> | |
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Foundations: | !Foundations: | ||
|- | |- | ||
− | | | + | |'''1.''' Through partial fraction decomposition, we can write the fraction |
|- | |- | ||
− | | | + | | <math style="vertical-align: -18px">\frac{1}{(x+1)(x+2)}=\frac{A}{x+1}+\frac{B}{x+2}</math> |
− | |||
|- | |- | ||
− | | | + | | for some constants <math style="vertical-align: -4px">A,B.</math> |
− | |||
|- | |- | ||
− | | | + | |'''2.''' Recall the Pythagorean identity |
− | |||
|- | |- | ||
− | | | + | | <math style="vertical-align: -5px">\sin^2(x)+\cos^2(x)=1.</math> |
− | |||
|} | |} | ||
+ | |||
'''Solution:''' | '''Solution:''' | ||
Line 32: | Line 29: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |We first | + | |We first note that |
|- | |- | ||
| | | | ||
− | + | <math>\int \frac{t^2}{\sqrt{1-t^6}}~dt=\int \frac{t^2}{\sqrt{1-(t^3)^2}}~dt.</math> | |
+ | |- | ||
+ | |Now, we proceed by <math>u</math>-substitution. | ||
|- | |- | ||
− | | | + | |Let <math style="vertical-align: 0px">u=t^3.</math> |
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: 0px">du=3t^2dt</math> and <math style="vertical-align: -14px">\frac{du}{3}=t^2dt.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\int \frac{t^2}{\sqrt{1-t^6}}~dt=\int \frac{1}{3\sqrt{1-u^2}}~du.</math> | |
− | \ | ||
− | |||
− | |||
− | |||
|} | |} | ||
Line 54: | Line 49: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now | + | |Now, we need to use trig substitution. |
|- | |- | ||
− | |Let <math style="vertical-align: | + | |Let <math style="vertical-align: -1px">u=\sin \theta.</math> Then, <math style="vertical-align: 0px">du=\cos \theta d\theta.</math> |
|- | |- | ||
|So, we have | |So, we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | \displaystyle{\int | + | \displaystyle{\int \frac{t^2}{\sqrt{1-t^6}}~dt} & = & \displaystyle{\int \frac{\cos \theta}{3\sqrt{1-\sin^2\theta}}~d\theta}\\ |
+ | &&\\ | ||
+ | & = & \displaystyle{\int \frac{\cos \theta}{3\sqrt{\cos^2\theta}}~d\theta}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\int \frac{\cos \theta}{3\cos \theta} d\theta}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\int \frac{1}{3}~d\theta}\\ | ||
+ | &&\\ | ||
+ | & = & \displaystyle{\frac{1}{3}\theta +C}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{ | + | & = & \displaystyle{\frac{1}{3}\arcsin(u)+C}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{ | + | & = & \displaystyle{\frac{1}{3}\arcsin(t^3)+C.} |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
Line 75: | Line 78: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we add and subtract <math style="vertical-align: 0px">x</math> from the numerator. | + | |First, we add and subtract <math style="vertical-align: 0px">x</math> from the numerator. |
|- | |- | ||
|So, we have | |So, we have | ||
Line 85: | Line 88: | ||
& = & \displaystyle{\int \frac{2x^2+x}{2x^2+x}~dx+\int\frac{1-x}{2x^2+x}~dx}\\ | & = & \displaystyle{\int \frac{2x^2+x}{2x^2+x}~dx+\int\frac{1-x}{2x^2+x}~dx}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{\int ~dx+\int\frac{1-x}{2x^2+x}~dx}.\\ | + | & = & \displaystyle{\int 1~dx+\int\frac{1-x}{2x^2+x}~dx}.\\ |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
Line 94: | Line 97: | ||
|Now, we need to use partial fraction decomposition for the second integral. | |Now, we need to use partial fraction decomposition for the second integral. | ||
|- | |- | ||
− | |Since <math style="vertical-align: -5px">2x^2+x=x(2x+1),</math> we let | + | |Since <math style="vertical-align: -5px">2x^2+x=x(2x+1),</math> we let |
|- | |- | ||
− | | | + | | <math>\frac{1-x}{2x^2+x}=\frac{A}{x}+\frac{B}{2x+1}.</math> |
− | |||
|- | |- | ||
− | |Multiplying both sides of the last equation by <math style="vertical-align: -5px">x(2x+1),</math> | + | |Multiplying both sides of the last equation by <math style="vertical-align: -5px">x(2x+1),</math> |
|- | |- | ||
− | | | + | |we get |
− | |||
|- | |- | ||
− | | | + | | <math style="vertical-align: -5px">1-x=A(2x+1)+Bx.</math> |
|- | |- | ||
− | + | |If we let <math style="vertical-align: -5px">x=0,</math> the last equation becomes <math style="vertical-align: -1px">1=A.</math> | |
− | |||
− | |||
− | |If we let <math style="vertical-align: - | ||
|- | |- | ||
− | | | + | |If we let <math style="vertical-align: -14px">x=-\frac{1}{2},</math> then we get <math style="vertical-align: -13px">\frac{3}{2}=-\frac{1}{2}\,B.</math> Thus, <math style="vertical-align: 0px">B=-3.</math> |
− | ::<math style="vertical-align: 0px">B=-3.</math> | ||
|- | |- | ||
− | |So, in summation, we have | + | |So, in summation, we have |
|- | |- | ||
− | | | + | | <math>\frac{1-x}{2x^2+x}=\frac{1}{x}+\frac{-3}{2x+1}.</math> |
− | |||
|} | |} | ||
Line 126: | Line 122: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
− | \displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{\int ~dx+\int\frac{1}{x}~dx+\int\frac{-3}{2x+1}~dx}\\ | + | \displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{\int 1~dx+\int\frac{1}{x}~dx+\int\frac{-3}{2x+1}~dx}\\ |
&&\\ | &&\\ | ||
− | & = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx} | + | & = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx.}\\ |
\end{array}</math> | \end{array}</math> | ||
|} | |} | ||
Line 136: | Line 132: | ||
!Step 4: | !Step 4: | ||
|- | |- | ||
− | |For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution. | + | |For the final remaining integral, we use <math style="vertical-align: 0px">u</math>-substitution. |
+ | |- | ||
+ | |Let <math style="vertical-align: -2px">u=2x+1.</math> | ||
|- | |- | ||
− | | | + | |Then, <math style="vertical-align: 0px">du=2\,dx</math> and <math style="vertical-align: -14px">\frac{du}{2}=dx.</math> |
|- | |- | ||
− | |Thus, our | + | |Thus, our integral becomes |
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx}\\ | \displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{x+\ln x+ \int\frac{-3}{2x+1}~dx}\\ | ||
&&\\ | &&\\ | ||
& = & \displaystyle{x+\ln x+\int\frac{-3}{2u}~du}\\ | & = & \displaystyle{x+\ln x+\int\frac{-3}{2u}~du}\\ | ||
&&\\ | &&\\ | ||
− | & = & \displaystyle{x+\ln x-\frac{3}{2}\ln u +C} | + | & = & \displaystyle{x+\ln x-\frac{3}{2}\ln u +C.}\\ |
\end{array}</math> | \end{array}</math> | ||
|- | |- | ||
Line 154: | Line 152: | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
+ | \displaystyle{\int \frac{2x^2+1}{2x^2+x}~dx} & = & \displaystyle{x+\ln x-\frac{3}{2}\ln (2x+1) +C.} | ||
+ | \end{array}</math> | ||
|} | |} | ||
Line 162: | Line 162: | ||
!Step 1: | !Step 1: | ||
|- | |- | ||
− | |First, we write | + | |First, we write |
|- | |- | ||
− | | | + | | <math style="vertical-align: -13px">\int\sin^3x~dx=\int \sin^2 x \sin x~dx.</math> |
|- | |- | ||
− | | | + | |Using the identity <math style="vertical-align: -5px">\sin^2x+\cos^2x=1,</math> we get |
− | + | |- | |
+ | | <math style="vertical-align: -1px">\sin^2x=1-\cos^2x.</math> | ||
|- | |- | ||
|If we use this identity, we have | |If we use this identity, we have | ||
|- | |- | ||
− | | <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx.</math> | + | | <math style="vertical-align: -13px">\int\sin^3x~dx=\int (1-\cos^2x)\sin x~dx.</math> |
+ | |- | ||
+ | | | ||
|} | |} | ||
Line 177: | Line 180: | ||
!Step 2: | !Step 2: | ||
|- | |- | ||
− | |Now, we proceed by <math>u</math>-substitution. Let <math>u=\cos x.</math> Then, <math style="vertical-align: -1px">du=-\sin x dx.</math> | + | |Now, we proceed by <math>u</math>-substitution. |
+ | |- | ||
+ | |Let <math>u=\cos x.</math> Then, <math style="vertical-align: -1px">du=-\sin x dx.</math> | ||
|- | |- | ||
|So we have | |So we have | ||
|- | |- | ||
| | | | ||
− | + | <math>\begin{array}{rcl} | |
\displaystyle{\int\sin^3x~dx} & = & \displaystyle{\int -(1-u^2)~du}\\ | \displaystyle{\int\sin^3x~dx} & = & \displaystyle{\int -(1-u^2)~du}\\ | ||
&&\\ | &&\\ | ||
Line 192: | Line 197: | ||
| | | | ||
|} | |} | ||
+ | |||
{| class="mw-collapsible mw-collapsed" style = "text-align:left;" | {| class="mw-collapsible mw-collapsed" style = "text-align:left;" | ||
!Final Answer: | !Final Answer: | ||
|- | |- | ||
− | |'''(a)''' <math> | + | | '''(a)''' <math>\frac{1}{3}\arcsin(t^3)+C</math> |
|- | |- | ||
− | |'''(b)''' <math style="vertical-align: -14px">x+\ln x-\frac{3}{2}\ln (2x+1) +C</math> | + | | '''(b)''' <math style="vertical-align: -14px">x+\ln x-\frac{3}{2}\ln (2x+1) +C</math> |
|- | |- | ||
− | |'''(c)''' <math style="vertical-align: -14px">-\cos x+\frac{\cos^3x}{3}+C</math> | + | | '''(c)''' <math style="vertical-align: -14px">-\cos x+\frac{\cos^3x}{3}+C</math> |
|} | |} | ||
[[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] | [[009B_Sample_Final_1|'''<u>Return to Sample Exam</u>''']] |
Latest revision as of 17:05, 20 May 2017
Compute the following integrals.
(a)
(b)
(c)
Foundations: |
---|
1. Through partial fraction decomposition, we can write the fraction |
for some constants |
2. Recall the Pythagorean identity |
Solution:
(a)
Step 1: |
---|
We first note that |
|
Now, we proceed by -substitution. |
Let |
Then, and |
So, we have |
|
Step 2: |
---|
Now, we need to use trig substitution. |
Let Then, |
So, we have |
|
(b)
Step 1: |
---|
First, we add and subtract from the numerator. |
So, we have |
|
Step 2: |
---|
Now, we need to use partial fraction decomposition for the second integral. |
Since we let |
Multiplying both sides of the last equation by |
we get |
If we let the last equation becomes |
If we let then we get Thus, |
So, in summation, we have |
Step 3: |
---|
If we plug in the last equation from Step 2 into our final integral in Step 1, we have |
|
Step 4: |
---|
For the final remaining integral, we use -substitution. |
Let |
Then, and |
Thus, our integral becomes |
|
Therefore, the final answer is |
|
(c)
Step 1: |
---|
First, we write |
Using the identity we get |
If we use this identity, we have |
Step 2: |
---|
Now, we proceed by -substitution. |
Let Then, |
So we have |
|
Final Answer: |
---|
(a) |
(b) |
(c) |